2019
DOI: 10.1017/jog.2019.66
|View full text |Cite
|
Sign up to set email alerts
|

Reanalysis of the US Geological Survey Benchmark Glaciers: long-term insight into climate forcing of glacier mass balance

Abstract: Mountain glaciers integrate climate processes to provide an unmatched signal of regional climate forcing. However, extracting the climate signal via intercomparison of regional glacier mass-balance records can be problematic when methods for extrapolating and calibrating direct glaciological measurements are mixed or inconsistent. To address this problem, we reanalyzed and compared long-term mass-balance records from the US Geological Survey Benchmark Glaciers. These five glaciers span maritime and continental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
93
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(101 citation statements)
references
References 93 publications
(152 reference statements)
8
93
0
Order By: Relevance
“…Their results are similar to our results for 1986–2005 for the same ice masses (area loss of 91 ± 22 km 2 , 4.2%). O'Neel and others (2019) found that the Wolverine glacier experienced a 1.5 km 2 area reduction between 1969 and 2018, which is similar to the area loss of 1.4 km 2 found in this study for the period 1986–2016.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Their results are similar to our results for 1986–2005 for the same ice masses (area loss of 91 ± 22 km 2 , 4.2%). O'Neel and others (2019) found that the Wolverine glacier experienced a 1.5 km 2 area reduction between 1969 and 2018, which is similar to the area loss of 1.4 km 2 found in this study for the period 1986–2016.…”
Section: Resultssupporting
confidence: 87%
“…Also, all five benchmark glaciers in Alaska (Gulkana, Wolverine, Lemon Creek, South Cascade and Sperry Glacier) have lost mass with average mass-balance rates ranging from −0.58 to −0.30 m w.e. a −1 since mid-20 th century (O'Neel and others, 2014; O'Neel and others, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…We assessed geodetic mass balance uncertainty from DEM accuracy and alignment, data gaps and density assumptions using methods identical to the USGS Benchmark Glacier Project (O'Neel and others, 2019). Errors from accuracy and alignment were quantified with the normalized median absolute deviation (NMAD) of post co-registration residual differences over stable, snow-free bedrock, between a given DEM and the reference DEM (Shean and others, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…We used a mass balance model (Van Beusekom and others, 2010; O'Neel and others, 2019) to adjust mid-season measurements to a consistent time system. A positive degree-day (PDD) model (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…South Cascade Glacier is a small mountain glacier that has an extensive history of scientific study (e.g. Krimmel, 1989; Fountain, 1994), in part due to its status as a USGS benchmark glacier (Meier, 1961; O'Neel and others, 2019). Seasonal mass-balance surveys have been performed here every spring and fall since 1959.…”
Section: Methodsmentioning
confidence: 99%